Effect of Communication and Physical Work Environment on Employee Performance of PT.Vadhana International Palembang Branch - Ririn Agustina (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of communication and physical work environment on the performance of employees of PT Vadhana International Palembang Branch. The data in this study used quantitative research. Then the source of data in this study is primary data. The population in this study were employees of PT. Vadhana International Palembang Branch, which had 72 employees. The sampling technique is done by total sampling or saturated sample or also called census sample, namely the sampling technique is done by taking the entire population because the total population is 72, then all populations are sampled. The data analysis technique in this study used SPSS v26. The results indicate that communication and physical work environment had a significant effect on employee performance. This research is useful for improving employee performance through communication and the company's physical work environment.